2015
DOI: 10.1038/jcbfm.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4-Loaded PLGA Microspheres Relieve Cerebral Ischemia/Reperfusion Injury and Neurologic Deficits through Long-Lasting Bioactivity-Mediated Phosphorylated Akt/eNOS Signaling in Rats

Abstract: Glucagon-like peptide-1 (GLP-1) receptor activation in the brain provides neuroprotection. Exendin-4 (Ex-4), a GLP-1 analog, has seen limited clinical usage because of its short half-life. We developed long-lasting Ex-4-loaded poly(D,L-lactide-co-glycolide) microspheres (PEx-4) and explored its neuroprotective potential against cerebral ischemia in diabetic rats. Compared with Ex-4, PEx-4 in the gradually degraded microspheres sustained higher Ex-4 levels in the plasma and cerebrospinal fluid for at least 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 39 publications
3
66
0
1
Order By: Relevance
“…Put together, with the general existence of crosstalk among the MAPK family, we speculate that different signal transduction pathways may be activated by different stimulations to regulate AQP4 expression. Moreover, the PI3K/Akt pathway was also demonstrated to regulate AQP4 expression [35]. As a result, it is not hard to explain our findings about AQP4 regulation pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Put together, with the general existence of crosstalk among the MAPK family, we speculate that different signal transduction pathways may be activated by different stimulations to regulate AQP4 expression. Moreover, the PI3K/Akt pathway was also demonstrated to regulate AQP4 expression [35]. As a result, it is not hard to explain our findings about AQP4 regulation pathways.…”
Section: Discussionmentioning
confidence: 91%
“…The timing of drug administration varied between studies. Eight studies administered GLP‐1RAs pre‐ischaemia , eight post‐ischaemia and four both pre‐ and post‐ischaemia . For the seven studies involving DPP‐4Is, one study applied the drugs pre‐ischaemia , one post‐ischaemia and five studies both pre‐ and post‐ischaemia .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the upregulation of AQP‐4 expression was involved in neuroinflammation and formation of the brain edema after stroke . SA decreased the expression of AQP‐4 protein in the hippocampus and basilar artery, which might contribute to the alleviation of brain injury after SAH.…”
Section: Discussionmentioning
confidence: 91%